Role of Retrograde Trafficking in Stress Response, Host Cell Interactions, and Virulence of Candida albicans - Liu, Yaoping (American Society for Microbiology, 2014)
In Saccharomyces cerevisiae, the vacuolar protein sorting complexes Vps51/52/53/54 and Vps15/30/34/38 are essential for efficient endosome-to-Golgi complex retrograde transport. Here we investigated the function of Vps15 and Vps51, representative members of these complexes, in the stress resistance, host cell interactions, and virulence of Candida albicans. We found that C. albicans vps15Δ/Δ and vps51Δ/Δ mutants had abnormal vacuolar morphology, impaired retrograde protein trafficking, and dramatically increased susceptibility to a variety of stressors. These mutants also had reduced capacity to invade and damage oral epithelial cells in vitro and attenuated virulence in the mouse model of oropharyngeal candidiasis. Proteomic analysis of the cell wall of the vps51Δ/Δ mutant revealed increased levels of the Crh11 and Utr2 transglycosylases, which are targets of the calcineurin signaling pathway. The transcript levels of the calcineurin pathway members CHR11, UTR2, CRZ1, CNA1, and CNA2 were elevated in the vps15Δ/Δ and vps51Δ/Δ mutants. Furthermore, these strains were highly sensitive to the calcineurin-specific inhibitor FK506. Also, deletion of CHR11 and UTR2 further increased the stress susceptibility of these mutants. In contrast, overexpression of CRH11 and UTR2 partially rescued their defects in stress resistance, but not host cell interactions. Therefore, intact retrograde trafficking in C. albicans is essential for stress resistance, host cell interactions, and virulence. Aberrant retrograde trafficking stimulates the calcineurin signaling pathway, leading to the increased expression of Chr11 and Utr2, which enables C. albicans to withstand environmental stress.